The Sufi Experience in Mahmoud Darwish's Poetry- the Hoopoe poem as a model - Ehtoob, Ismail Mahmoud (Journal of Humanities & Social Sciences, 2021)
This study is based on the analysis of the influence of Sufi thought on the poet Mahmoud Darwish in the poem "Hoopoe", which is combined with the book of Farid al- Din al- Attar "The Logic of the Bird." It turns out that Darwish turned to the world of brightness in order to take advantage of the mystical terminology of immersion, depth in the image, and difficulty in coding. In fact, his textual relevance in this experiment is not limited to his crucible in the crucible of "bird logic" alone, but extends to all sources of Persian mysticism, and therefore the researcher sought to reveal the references between the "bird logic" and the foundations of Sufi thought, and then monitor their reflections, taking into account Consider that the issue of belonging to the land or shifting from it is one of the most serious issues in the process of Mahmoud Darwish, and the reason is the stark contrast between his revolutionary and Sufi tolerant thought.
Keywords: Darwish; Sufism; Hoopoe; Attar